El arbitraje como mecanismo alternativo de solución de conflictos y responsabilidades penales derivadas de él: algunas notas - Puente Rodríguez, Leopoldo (2025)
Arbitration has emerged as a prominent alternative to judicial adjudication for the resolution of disputes, gaining substantial social and economic significance. Despite its growing prominence, the role of criminal law in regulating and addressing misconduct within the arbitral process remains underexplored. This article posits that the existing criminal law framework is insufficiently equipped to effectively respond to potential criminal phenomena arising in the context of arbitration. Considering this, the study examines the current provisions and available responses within the Peruvian and Spanish criminal codes, highlighting both their strengths and limitations in confronting the unique challenges posed by arbitration-related offences.